An Analysis of the Modern Audit of Marketing Strategy Procedures of Coca-Cola and How it Affected the Internationally Renowned Company - Carle, Max Ralph (2021)
The ‘Share a Coke’ marketing campaign started in 2011 in Australia and afterwards spread around the world. Coca-Cola personalized bottles with popular names, songs, vacation destinations and everyday heroes. The aim of this bachelor’s thesis is to carry out a marketing audit, which analyzes the ‘Share a Coke’ marketing campaign of Coca-Cola and offers practical solutions for the issues encountered along the way. Accounting data was used and analysed from the perspective of an internal auditor to measure the company’s success. Overall, the objective of the campaign was to establish a personal relationship and let the public drive the campaign through social media channels. It was the first marketing campaign to increase sales of Coca-Cola within the past 10 years. The evaluation of this marketing strategy showed that it was extremely successful, although it raised smaller issues. An example is that the public criticized it for a lack of inclusivity, since some names were left out in the personalization stage. The public was not able to select names from certain regions in the world. Coca-Cola remains the clear market leader, and the campaign truly solidified its dominance around the world in the industry of non-alcoholic beverages.